Total arch replacement with separated graft technique and selective antegrade cerebral perfusion - Kazui, Teruhisa (Annals of Cardiothoracic Surgery; Vol 2, No 3 (May 30, 2013): Aortic arch surgery (II), 2013)
It is essential to select the optimum method of cerebral protection and operative technique for arch repair to improve the surgical outcome of arch aneurysm or dissection. Selective antegrade cerebral perfusion (SACP) is our current method of choice if required cerebral protection time exceeds 30 minutes. Moderate hypothermic two-arch vessel perfusion (innominate artery or right axillary artery and left common carotid artery) is safe and effective for brain protection in a majority of patients. The separated graft technique using 4-branched graft is now our preferred surgical procedure used for arch aneurysm or dissection because this technique presents several advantages over the en-bloc or island technique. SACP allows us to perform meticulous arch repair and facilitates the time-consuming total arch replacement for complex aortic arch pathology and results in an acceptable mortality (less than 4%) and morbidity (stroke 3%).